Burned-Out Testicular Tumors in Adolescents: Clinical Aspects and Outcome - Persano, Giorgio; Crocoli, Alessandro; De Pasquale, Maria Debora; Cozza, Raffaele; Alaggio, Rita; Diomedi Camassei, Francesca; Beati, Federico; Di Paolo, Pierluigi; Martucci, Cristina; Inserra, Alessandro (Frontiers in Pediatrics, 2021)
Purpose Testicular germ cell tumors are the fourth most common neoplasm in adolescents, accounting for 8% of all tumors in the age group 15 – 19 years. On rare instances, the primary testicular lesion is not clinically nor radiologically evident whilst nodal or visceral metastases represent the clinical manifestations of the disease. This phenomenon is described as “burned-out testicular tumor”. In this paper the authors report a single institution experience with burned out testicular tumors in adolescents and discuss their clinical implications. Patients and Methods All the patients diagnosed with metastatic testicular germ cell tumors at Bambino Gesù Children Hospital between 1st January 2010 and 30th June 2020 were included in the study. Patients were categorized in two groups: “primary testicular” and “burned out”. All the patients were staged and treated according to the AIEOP – TCGM 2004 protocol Results Eleven patients were classified as “primary testicular”, five patients were classified as “burned out”. “Burned out” tumors were associated with the presence of systemic symptoms compared to “primary testicular” tumors (80% vs 0%; p = 0.0027) and higher aFP, hCG and LDH levels (p < 0.00001). “Burned out” population had a statistically significant higher incidence of relevant toxicity than “primary testicular” population (80% vs 18%; p = 0.0357) and a worse outcome both in terms of mean overall survival (15 vs 43 months; p = 0.0299) and mean event-free survival (12 vs 38 months; p = 0.0164). Conclusion “Burned out” testicular tumors seem to be a well distinct clinical entity with a high treatment-related toxicity and poor prognosis. Further studies are needed to clarify the “burned-out phenomenon” and to identify more effective therapeutic strategies for these patients